The professor, "Angry Amy" - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case examines the issue of companies running criminal background checks when hiring someone. Amy Bishop shot her peers when she was denied tenure at the University of Alabama at Huntsville. Apparently, Bishop was accused of several other crimes, including killing her brother when she was 21 and a student at Northeastern University.